Takotsubo Syndrome in the Perioperative Period: A Case Report and a Comprehensive Review of Pertinent Literature. Issue 6 (8th June 2022) - Seretis, Konstantinos; Bounas, Nikos; Vaikos, Dimitrios; Athanasiadis, Ilias
Abstract : Supplemental digital content is available in the text. Abstract: Stress-induced cardiomyopathy or takotsubo syndrome is a rare, nonischemic, heart condition resembling that of an acute coronary syndrome. Its distinctive feature is a transient wall motion abnormality occurring usually at the apical segment of the heart, with the degree of symptom manifestation and severity varying among patients. Although early data were supportive of a benign sequela and outcome, high degree of adverse events, such as acute heart failure and pulmonary edema, are anticipated, and the mortality rate approaches 5%. Hyperactivation of the sympathetic nervous system and adrenergic drugs have been pointed out as possible precipitators of the condition. Surgical procedures are a known cause of emotional and physical stress on patients, acting as an ideal substrate for the presentation of this syndrome. On occasion of a perioperative takotsubo syndrome case in a female patient during second-stage implant-based breast reconstruction, a review of the pertinent literature is presented. The acute onset and severity of the manifestations in this surgically uneventful procedure necessitated a multidisciplinary approach. Consequently, this report should raise awareness of the syndrome among plastic surgeons and anesthesiologists to promptly recognize and manage it effectively.